2011
DOI: 10.1093/sleep/34.2.235
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Type and Bed-Timing Regularity in 654 Retired Seniors: Correlations with Subjective Sleep Measures

Abstract: In retired seniors, a morning-type orientation and regularity in bedtimes and rise-times appear to be correlated with improved subjective sleep quality and with less time spent in bed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…In agreement with our earlier analysis of a subset (~69%) of these data (Monk et al, 2011), M-types reported 23 min shorter TST than did O-types (443 versus 466 min, t = 4.56, p <0.001).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with our earlier analysis of a subset (~69%) of these data (Monk et al, 2011), M-types reported 23 min shorter TST than did O-types (443 versus 466 min, t = 4.56, p <0.001).…”
Section: Resultssupporting
confidence: 92%
“…In an older adult sample (Monk et al, 2011), we have shown (in a subset of the present study of retired seniors – see below) that when Total Sleep Time (TST = time spent in bed minus time in unwanted wakefulness) was assessed using the Sleep Timing Questionnaire (STQ) (Monk et al, 2003), there was an apparent paradox in that M-types reported significantly less actual sleep being obtained than was obtained by O-types. Thus, although seniors who retire to bed earlier report more sleep than those with later bedtimes, seniors who are M-types appeared to report less sleep than seniors who are O-types, even though they go to bed significantly earlier than O-types.…”
Section: Introductionmentioning
confidence: 67%
“…Other aspects of this study have been and will be reported elsewhere. 18,19 Among other variables, the interview included telephone versions of the Pittsburgh Sleep Quality Index (PSQI), 20 the Epworth Sleepiness Scale (ESS) 21 and the Sleep Timing Questionnaire (STQ). 22 The aim of this analysis was to provide normative empirical data regarding these variables in a sample of Western Pennsylvanian retirees.…”
Section: Introductionmentioning
confidence: 99%
“…Cross-sectional studies illustrate that high daily lifestyle regularity, including high regularity in sleep timing, is associated with better subjective sleep in college students (Carney et al, 2006), young and middle-aged adults (Monk et al, 2003a), and seniors (Zisberg et al, 2010). Stable bedtimes and rise-times have been found to be related to better sleep quality in retired older adults without the constraints of daytime work (Monk et al, 2011). In a prospective study, irregularity in sleep-wake timing also predicted daytime sleepiness (Manber et al, 1996).…”
Section: Introductionmentioning
confidence: 99%